Mandibular Advancement Devices in OSA Patients: Impact on Occlusal Dynamics and Tooth Alignment Modifications—A Pilot Prospective and Retrospective Study - Aylin Uyaner; Helen Schneider; Aditya Parikh; Kathrin Paeske-Hinz; Anna Konermann (Dentistry Journal)
Background: The widespread prevalence of obstructive sleep apnea (OSA) underscores the necessity for effective therapies. Mandibular advancement devices (MADs) have emerged as valid treatment for mild to moderate cases, despite the associated dental side effects. Methods: This study evaluates the nature, onset, and long-term manifestation of these side effects. In the prospective group (n = 12), dental impressions were taken pre-MAD-insertion and at intervals of three, six, nine, and twelve months post-insertion to monitor occlusal alterations. In the retrospective group, participants (n = 8) wearing MADs for 7 years at average underwent lateral cephalogram assessments to compare with pre-treatment X-rays. All participants completed a specific questionnaire. Statistical analysis was performed via t-test and with p < 0.05 as the significance level. Results: The majority of participants in both groups consistently used MADs and reported significant sleep quality improvements, rating common symptoms like jaw tension as negligible. In both the prospective group and the retrospective group, significant reductions in overjet were observed at multiple time points, with the prospective group showing reductions at six months (p = 0.001), nine months (p > 0.001), and twelve months (p = 0.019), while the retrospective group indicated a notable decrease between baseline and follow-up assessments after a mean of seven years of device wear (p = 0.004). A slight overbite increase of 0.2 mm was prospectively observed after one year, whereas a trend towards a minimal decrease over the long term was observed in the retrospective sample (p = 0.003). Noteworthy changes in angle class or lower incisor inclination were absent. Cephalograms revealed significant IOK-NL angle alterations with a mean of 98.2° before and 95.2° upon long-term treatment (p = 0.020). Conclusions: These findings suggest that MADs are effective in treating OSA with minor adverse effects. This study advocates for moderate mandibular protrusion to balance therapeutic efficacy with dental health considerations, crucial for optimizing treatment outcomes. Nonetheless, the limited sample size warrants caution when generalizing these results to the broader population.